Pengaruh Pemberian ASI Fase Kolostrum Terhadap Kejadian ISPA Pada Balita di Poli Anak RS Panti Nirmala Malang - Nurul Anjarwati; Wiwit Nurwidyaningtyas; Fitri Nur Ika Revliawan; La Saudi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
ARI is an acute infection involving the lower respiratory tract organs caused by viruses, fungi and bacteria which often occurs in children under five years and still ranks as the highest cause of infant mortality, one of the influencing factors is the lack of exclusive breastfeeding. The aim of this research is to determine the effect of colostrum phase breastfeeding on the incidence of ARI in toddlers. This type of research is observational using a cross sectional design with a quantitative approach. The population in this study were all toddlers with ARI who came to the Children's Polyclinic at Panti Nirmala Hospital Malang (data October - November 2023), the sampling technique used consecutive sampling of 128 people. The research instrument used a questionnaire, analysis used chi-square. The results of the study showed that most of the colostrum phase breastfeeding (59.4%) was categorized as not being given breast milk, the incidence of ARI in toddlers was found to be almost half (35.3%) categorized as mild ARI, and the results of the chi-square analysis showed a p value of 0.000, which means the data was declared significant and Ha was accepted, meaning that colostrum phase breastfeeding had a significant effect on the incidence of ARI in toddlers at the Children's Polyclinic at Panti Nirmala Hospital, Malang. Parents of toddlers are expected to give colostrom phase breast milk exclusively to their babies from birth until 7 days of age, this is because colostrom phase breast milk is the best source of nutrition and protection for babies, because it can improve the baby's immune system and prevent respiratory tract infections. Health workers are expected to be able to provide education and counseling to pregnant and breastfeeding mothers about the importance of colostrom phase breastfeeding for the baby's health